IJTIHAD DAN KONTEKSTUALISASI HUKUM ISLAM - Muhammad Sulthon (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2019)
Science and technology development now days has caused the problems faced by islamic society become more and more complex. The study on law product has to be counducted and reexamined for answering the problems and finding the solotions. Therefore, ijtihad one of the methods used by several mujtahids, either fardi ijtihad or jama’i ijtihad. A number of mujtahids from various diciplines are needed to make more reliable decisions.This article will describe the role of ijtihad in the process of islamic law formation.